Father Involvement and Adolescent Klitih Prevention: A Bibliometric Perspective on Family Counseling Interventions - Pram Bagus Panuntun; Azam Syukur Rahmatullah (Universitas PGRI Yogyakarta, 2026)
This bibliometric study explores the research landscape on father involvement in parenting as a foundation for family counseling interventions to prevent klitih behavior among adolescents. Data were collected from Scopus and Web of Science (2014–2024), yielding 1,245 publications. Bibliometric mapping and trend analysis were conducted using VOSviewer, Biblioshiny, and R-Studio. Findings identified four major clusters: father involvement and child development (38%), family counseling interventions (29%), adolescent risk behaviors and violence (21%), and cultural contexts in parenting (12%). Research output increased substantially, from 45 articles in 2014 to 187 in 2024, with peak interest between 2020-2022. The United States led contributions (34%), followed by Australia (18%) and the United Kingdom (15%), while Southeast Asia accounted for only 6%. Key frameworks included Attachment Theory, Family Systems Theory, and Social Learning Theory. The study highlights research gaps in culturally specific interventions and emphasizes the need for father-focused counseling models to prevent adolescent violence. Keywords: father involvement, klitih behavior, family counseling, adolescent violence prevention, Yogyakarta, bibliometric analysis